MOBILE TRAINING UNIT MANAGEMENT IN YOUTH EMPOWERMENT IN MUSHROOM CULTIVATION TRAINING AT UPT WORK TRAINING CENTER, JEMBER - Rakadewa, Elang; Hendrawijaya, A.T; Indrianti, Deditiani Tri; Hilmi, Muhammad Irfan (Universitas Pendidikan Indonesia (UPI), 2022)
In this modern era, there are many problems that arise in the community, one of them is the difficulties to find a job because of lack experience. Training is very important to our lives. Nowdays, there are a lot of training institutes. However, the majority of the training institutions are located on the town while Therefore, come up a innovation that is Mobile Training Units (MTU) that will be an innovation for them who are still got difficulties to reach the training location. This research used a qualitative. UPT BLK Jember is a research area using purposive area, observations, interviews, and documentations. The technique of determining the research participants is using a snowball sampling, then the informant is the management and participant . The data analysis is done by using Miles and Huberman models i.e. data collection, data reduction, data percentation, and conclusions. The conclusion of this research is management that is conducted by the instructor of UPT BLK has been effective and efficient in empowering the trainees.